Malignant melanoma S3-guideline "diagnosis, therapy and follow-up of melanoma" - Pflugfelder, Annette; Kochs, Corinna; Blum, Andreas; Capellaro, Marcus; Czeschik, Christina; Dettenborn, Therese; Dill, Dorothee; Dippel, Edgar; Eigentler, Thomas; Feyer, Petra; Follmann, Markus; Frerich, Bernhard; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2013)
This first German evidence-based guideline for cutaneous melanoma was developed under the auspices of the German Dermatological Society (DDG) and the Dermatologic Cooperative Oncology Group (DeCOG) and funded by the German Guideline Program in Oncology. The recommendations are based on a systematic literature search, and on the consensus of 32 medical societies, working groups and patient representatives. This guideline contains recommendations concerning diagnosis, therapy and follow-up of melanoma. The diagnosis of primary melanoma based on clinical features and dermoscopic criteria. It is confirmed by histopathologic examination after complete excision with a small margin. For the staging of melanoma, the AJCC classification of 2009 is used. The definitive excision margins are 0.5 cm for in situ melanomas, 1 cm for melanomas with up to 2 mm tumor thickness and 2 cm for thicker melanomas, they are reached in a secondary excision. From 1 mm tumor thickness, sentinel lymph node biopsy is recommended. For stages II and III, adjuvant therapy with interferon-alpha should be considered after careful analysis of the benefits and possible risks. In the stage of locoregional metastasis surgical treatment with complete lymphadenectomy is the treatment of choice. In the presence of distant metastasis mutational screening should be performed for BRAF mutation, and eventually for CKIT and NRAS mutations. In the presence of mutations in case of inoperable metastases targeted therapies should be applied. Furthermore, in addition to standard chemotherapies, new immunotherapies such as the CTLA-4 antibody ipilimumab are available. Regular follow-up examinations are recommended for a period of 10 years, with an intensified schedule for the first three years.
EVALuna2:39292